Contemporary vision of architecture that is in harmony with its place - Alshaikh, Ramzy; said, Nassiba; issa, Yara (Latakia University Journal -Engineering Sciences Series, 2019)
يهتم البحث بمعالجة العلاقة بين العمارة ومكانها حيث تأخذ هذه العلاقة أشكالاً متعددة تتدرج من التلاحم وتمر بالحيادية حتى تصل إلى التنافر مع المكان. حيث ضعف الانتماء المكاني والإحساس بالمكان في العمارة المعاصرة فكانت الدعوة لاتجاه جديد يمثل طرازا دوليا له مفردات جديدة تتمثل في الأسقف الأفقية والأسطح المستوية واستخدام مواد جديدة كالخرسانة المسلحة والحديد والألواح الزجاجية دون النظر للاعتبارات البيئية والعمارة المحلية الخاصة بكل منطقة. وبالرغم من انتشار هذا الطراز الدولي للعمارة في مختلف دول العالم ظهرت اتجاهات ومفاهيم فكرية معاصرة أخرى اهتمت بالمكان كل منها بنظرة مختلفة ويعمل البحث على دراستها وتحليل بعض الحلول المعمارية وذلك بعد تحديد عناصر المكان (الموقع– المناخ– المحيط) ومن ثم رصد هذه العلاقة في هذه المفاهيم والحلول ثم يقوم باستخلاص الأفكار التصميمية التي اتبعتها لاعتمادها كمعايير يمكن استخدامها للوصول إلى علاقة واضحة بين العمارة ومكانها بكل عناصره. ويتم تقييم هذه الأفكار حسب قدرتها على التفاعل مع المكان سواء بالانسجام معه أو التغيير فيه بشكل يضيف إليه قيمة جمالية ووظيفية. The research cares about the relation between the architecture and its place, this relation takes different shapes ranging from the cohesion and go neutral until it reaches to the disharmony with the place. That the sense of the place decreased in the contemporary architecture, therefore there was an invitation to a new. Direction forms international models which has a new vocabulary represented in the horizontal ceilings and flat surfaces and the use of new materials as the reinforced concrete, iron, and glass panels without taking in concern the environmental considerations and the architecture of each local area. Despite the prevalence of this international type of architecture in various countries around the world, many contemporary theories and intellectual directions which focused on the place in different ways appeared, so the research is studying and analyzing these directions, after identifying the elements of the place (location- climate- surrounding neighborhood), then notice this relationship in these concepts and solutions, and try to reach to the design ideas that it follow it to adopt it as criteria which can be used to reach for a clear relationship between building and its places. And these ideas will be evaluated by their ability to interact with the place, both in harmony with it or change it in way make it better.